Is MDM2 SNP309 Variation a Risk Factor for Head and Neck Carcinoma?: An Updated Meta-Analysis Based on 11, 552 Individuals. Issue 9 (March 2016) - Zhuo, Xianlu; Ye, Huiping; Li, Qi; Xiang, Zhaolan; Zhang, Xueyuan
Abstract : Abstract: Murine double minute-2 (MDM2) is a negative regulator of P53, and its T309G polymorphism has been suggested as a risk factor for a variety of cancers. Increasing evidence has shown the association of MDM2 T309G polymorphism with head and neck carcinoma (HNC) risk. However, the results are inconsistent. Thus, we performed a meta-analysis to elucidate the association. The meta-analysis retrieved studies published up to August 2015, and essential information was extracted for analysis. Separate analyses on ethnicity, source of controls, sample size, detection method, and cancer types were also conducted. Odds ratios (ORs) and their 95% confidence intervals (CIs) were used to estimate the association. Pooled data from 16 case–control studies including 4625 cases and 6927 controls failed to indicate a significant association. However, in the subgroup analysis of sample sizes, an increased risk was observed in the largest sample size group (>1000) under a recessive model (OR = 1.52; 95% CI = 1.08–2.13). Increased risks were also found in the nasopharyngeal cancer in the subgroup analysis of cancer types (GG vs TT: OR = 2.07; 95% CI = 1.38–3.12; dominant model: OR = 1.48; 95% CI = 1.13–1.93; recessive model: OR = 1.76; 95% CI = 1.17–2.65). The results suggest that homozygote GG alleles of MDM2 SNP309 may be a low-penetrant risk factor for HNC, and G allele may confer nasopharyngeal cancer susceptibility.